Glucagon-Like Peptide 1 and the Cardiovascular System - Fava, Stephen (Current Diabetes Reviews, 2014)
Glucagon-like peptide 1 (GLP1) is a major incretin hormone. This means that it is secreted by the gut in response to food and helps in reducing post-prandial glucose exertion. It achieves this through a number of mechanisms, including stimulating insulin release by pancreatic β-cells in a glucose-dependent manner; inhibition of glucagon release by pancreatic α-cells (also in a glucose-dependent manner); induction of central appetite suppression and by delaying gastric empting thereby inducing satiety and also reducing the rate of absorption of nutrients. However, GLP1 receptors have been described in a number of extra-pancreatic tissues, including the endothelium and the myocardium. This suggests that the physiological effects of GLP1 extend beyond post-prandial glucose control and raises the possibility that GLP1 might have cardiovascular effects. This is of importance in our understanding of incretin hormone physiology and especially because of the possible implications that it might have with regard to cardiovascular effects of incretin-based therapies, namely DPP-IV inhibitors (gliptins) and GLP1 analogues. This review analyzes the animal and human data on the effects of GLP1 on the cardiovascular system in health and in disease and the currently available data on cardiovascular effects of incretin-based therapies. It is the author’s view that the physiological role of GLP1 is not only to minimize postprandial hypoglycaemia, but also protect against it.
Keywords: incretin